2021
DOI: 10.2460/javma.20.07.0418
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of outcomes following subtotal colectomy for the treatment of idiopathic megacolon in cats

Abstract: OBJECTIVE To evaluate outcomes in cats undergoing subtotal colectomy for the treatment of idiopathic megacolon and to determine whether removal versus nonremoval of the ileocecocolic junction (ICJ) was associated with differences in outcome. ANIMALS 166 client-owned cats. PROCEDURES For this retrospective cohort study, medical records databases of 18 participating veterinary hospitals were searched to identify records of cats with idiopathic megacolon treated by subtotal colectomy from January 2000 to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…In this study, the most presenting cats with megacolon were domestic shorthair breeds, which is comparable to another study where 61.4% of cats were domestic shorthairs (17). We also found male cats were presented with 6.1 years (SD: 3.05) median age and 4.3 kg (SD: 0.87) weight, relative to another study where they reported the median age and weight of the affected cats were 8.6 years and 5.3 kg, respectively (17).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this study, the most presenting cats with megacolon were domestic shorthair breeds, which is comparable to another study where 61.4% of cats were domestic shorthairs (17). We also found male cats were presented with 6.1 years (SD: 3.05) median age and 4.3 kg (SD: 0.87) weight, relative to another study where they reported the median age and weight of the affected cats were 8.6 years and 5.3 kg, respectively (17).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, cats with idiopathic megacolon had obstipation (tenesmus without defecation), which is similarly presented by another study, as the principal clinical sign (17). Obstipation means there is no bowel motility, whereas constipation means there are about ≤3 bowel motility per week (5).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations